2013
DOI: 10.12816/0001610
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Returns Risk for Islamic Investors

Abstract: For Islamic investors, sequencing risk is an omnipresent factor for retirement outcomes. This study shows that simple diversification can provide benefits to reducing the impact of sequencing risk. However, the results from the accumulation and distribution phases suggest that retirement products need to consider approaches that go beyond the received set-andforget approach. The findings point rather to a more dynamic, whole-of-life approach to be adopted by Islamic retirement products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…(Sania & Deo, 2013) proved that Indian Shariah market was predictable with macroeconomic indicators during the study period and necessary policy measures need to be taken to correct those since Shariah principle prohibits speculation and abnormal profit. (Doran et al 2013) also points out the benefits of investing in Shariah compliant shares so as to diversify the risk.…”
Section: Preludementioning
confidence: 99%
See 1 more Smart Citation
“…(Sania & Deo, 2013) proved that Indian Shariah market was predictable with macroeconomic indicators during the study period and necessary policy measures need to be taken to correct those since Shariah principle prohibits speculation and abnormal profit. (Doran et al 2013) also points out the benefits of investing in Shariah compliant shares so as to diversify the risk.…”
Section: Preludementioning
confidence: 99%
“…Since ARCH (1) doesn't capture adequately the volatility persistence found in asset returns, it is extended into ARCH (M) or ARCH Mean model by including GARCH (1, 1) model .In the attempt to find out the patterns in modelling and heteroscedasticity 11 in the returns the ARCH LM test 12 was employed and it was found that there was no homoscedasticity in the returns which even gives further scope for volatility clustering. 3it is clearly found that the ARCH effect and null hypothesis of CNX 500, CNX nifty and S&P BSE Tasis 50 could not be accepted since the F statistics and observed R 2 were significant at 1%.…”
Section: Modelling Garch Techniquesmentioning
confidence: 99%